Assessing tourism capital using two-tiered empirical model - Wadie Othmani; Rym Ammar (Annals of Tourism Research Empirical Insights)
The study aims to develop a novel approach to assess Tourism Capital in resort areas, specifically Zermatt-Matterhorn, between 2014 and 2021. This approach integrates a two-tiered empirical model, where the first tier involves CNN-based image analysis, and the second tier employs mathematical techniques and time-series social media data to evaluate stakeholder engagement. The research emphasizes how fluctuations in tourism capital are influenced by stakeholder interactions and external events, highlighting the significance of empirical and quantitative approaches in understanding tourism dynamics. The findings underscore the substantial role of stakeholder engagement in shaping overall tourism capital, offering a practical and dynamic tool for tourism analysis and urban planning. This study innovatively assesses Tourism Capital by analyzing Instagram images, offering a more in-depth, data-driven view of tourism development in resorts.